The Effects of Product Quality and Brand Image on Purchasing Decisions (Case Study: Kaliombo Coffee Shop) - Putra, Demmy Filsafa Ratna; Khusniyah, Khusniyah; Mardatilla, Indana (Manajemen Agribisnis: Jurnal Agribisnis, 2024)
Coffee is Indonesia's mainstay agricultural commodity and an export earner in addition to palm oil. National coffee production in aggregate increased from 2017-2022 by 5.31%. This is in line with the increase in coffee consumption in Indonesia which grew by around 8.22% per year from 2017-2022.The location of the research was conducted at Kaliombo Coffee Shop, City District, Kediri City. Respondents Kaliombo Coffee Shop at least have made purchases 2 times. Data collection methods with 2 types of data, namely primary data and secondary data. Primary data obtained with questionnaire tools distributed to research respondents at Kaliombo Coffee Shop and using multiple linear regression analysis. Based on the output above, R Square is 0.611, this means that the variables X1 (product quality) and X2 (brand image) simultaneously affect variable Y (purchase decision) by 61.1% and the remaining 29.9% is influenced by other factors. This emphasizes that product quality and brand image are critical to consumer purchasing decisions and offers practical implications for businesses in the coffee industry. The rigorous research methodology and clear presentation of the outcome of the study enhance its relevance academically and practically, making it a valuable contribution to understanding consumer behavior and making strategic decisions in a competitive market.